ANALISIS KETERAMPILAN GURU MENGELOLA KELAS DALAM MENUMBUHKAN MINAT BELAJAR SISWA KELAS IV DI SDI PLUS AL-IJTIHAD KOTA TANGERANG - Siti Ummu Habibah; Nurul Muttaqien; Yoyoh Fathurrohmah (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
In carrying out learning activities in the classroom, of course, there must be problems and obstacles experienced by teachers in learning activities, such as interest in learning. Teachers must understand that all students do not show the same interest in learning. For this reason, the teacher should indeed try to make his students while studying have an interest or interest in the material being taught. So the need for effective classroom management, to foster student learning interest. This study seeks to determine to what extent the teacher's ability in classroom management contributes to fostering student interest in the learning process. The subjects of this study were 1 class IV teacher and 26 class IV students. The method used is a type of descriptive qualitative research. The data analysis technique was carried out by qualitatively descriptive. The study's findings indicate that the teacher's abilities in class management are already effective in encouraging student learning interest, which is nevertheless low due to poor student learning motivation.